Mediating effects of organizational culture on the relationship between organizational context and organizational performance / Mohammed Abdullah Ali Alkhawlani - Ali Alkhawlani, Mohammed Abdullah (Institute of Graduate Studies, UiTM, 2016)
This research examine the construct relationships between organizational structure, strategy, and the congruence between structure and strategy in terms of organizational context, and their effect on organizational performance, then examine the effect of organizational culture as a mediator between these relationships. A total of 216 of Yemen airways non-managerial employees from four main departments participate in the study. The main objective of the study was to examine the significant of organizational culture as a plausible mediator between the congruence of organizational structure, and strategy and organizational performance and then between organizational structure, strategy and organizational performance. The findings stated that an organizational culture significantly and partially mediate the relationship between organizational context and organizational performance. Similarly, organizational culture significantly and partially mediates the relationship between organizational structure and organizational strategy. Other objective is to identify the effect of organizational context on organizational performance and organizational culture. The findings reported that organizational context is positively effects on organizational performance and organizational culture. Then the next objective is to determine the effect of organizational culture on organizational performance, and the finding is organizational culture has a significant correlation with the organizational performance. Last objective is to identify the effect of organizational structure and organizational strategy on organizational performance and organizational culture. In this objective the research findings stated that organizational strategy has a positive effect on organizational culture and organizational performance…